Synthesis, Spectral Characterization and Pharmacological Significance of Cr(III) and Mn(II) Complexes with Schiff Base and Thiocyanate Ion as Ligands (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
Cr(III) and Mn(II) metal complexes of Schiff base ligand derived from phenylacetylurea condensed with salicylaldehyde (SBPS) and thiocyanate(SCN-) ion were synthesized by using microwave irradiation. Microwave assisted synthesis gives high yield of the complexes within a very short time. The molecular formulae and the geometry of the complexes have been deduced from elemental analysis, metal estimation, electrical conductance, magnetic moment, electronic spectra, FT- IR, Far IR spectra, cyclic voltammetry, thermal analysis and powder-XRD techniques. The molar conductance values indicate that the complexes are non-electrolyte (1:0) type. FT-IR spectra show that Schiff base and thiocyanate ion are coordinated to the metal ion in a monodentate manner. The electronic spectra and the magnetic moment indicate the geometry of the complexes is found to be octahedral. The antimicrobial activities of ligands and their Cr(III) and Mn(II) complexes were studied against the microorganisms, viz., E. coli, Klebsiella Pneumonia, P. aeruginosa, S. aureus, Bacillus cereus, Aspergillus flavus, Aspergillus niger, Aspergillus oryzae, Aspergillus sojae and Candida albicans by agar well diffusion method. The complexes show moderate activity against the bacteria and enhanced activity against the fungi as compared to free SBPS ligand. The free radical scavenging activity of the complexes and the ligands has been determined by measuring their interaction with the stable free radical, DPPH. The complexes have larger antioxidant activity as compared to the ligand. DNA-binding properties have been studied by fluorescence-emissions method. The results suggest that the complexes strongly bind to DNA because of metal complexes are well-known to speed up the drug action and the ability of a therapeutic agent which can frequently be enhanced upon coordination with a metal ion.